Repurposing expired Remdesivir as a sustainable anti-corrosion agent for plain steel in HCl medium : Insights from electrochemical and molecular dynamics studies - Ali, Ismat H.; Sharifi, Ruhollah; Javidparvar, Ali Asghar; Nwanonenyi, Simeon C.; Oguzie, Emeka E.; Manfo, Theodore A. (Elsevier, 2025)
The COVID-19 pandemic has led to a surplus of expired pharmaceuticals, such as Remdesivir, posing environmental challenges. This study innovatively repurposes expired Remdesivir as a highly effective sustainable anti-corrosion agent for St12 mild steel in a 1 M HCl environment. Experimental and computational analyses reveal that Remdesivir’s molecular structure, featuring nitrogen and oxygen heteroatoms and multiple benzene rings, enables strong chemisorption on the steel surface, forming a dense protective layer. At an optimal concentration of 1000 ppm, Remdesivir achieves over 97 % corrosion inhibition efficiency. Molecular dynamics simulations confirm a spontaneous and stable interaction, with binding energies of −205.69 kcal/mol (gaseous phase) and −144.314 kcal/mol (solvated phase), highlighting its durable protective capabilities. This work not only offers an eco-friendly solution for managing expired drugs but also demonstrates their potential to enhance the longevity of metallic structures in corrosive environments, combining environmental sustainability with industrial applicability.
Keywords: corrosion; steel; inhibition; Remdesivir; electrochemical and molecular dynamics; fi=Sähkötekniikka|en=Electrical Engineering|